2017
DOI: 10.3961/jpmph.15.061
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tobacco Habits, Attitudes, and Education Among Medical Students in the United States and Italy: A Cross-sectional Survey

Abstract: ObjectivesMedical students represent a primary target for tobacco cessation training. This study assessed the prevalence of medical students’ tobacco use, attitudes, clinical skills, and tobacco-related curricula in two countries, the US and Italy, with known baseline disparities in hopes of identifying potential corrective interventions.MethodsFrom September to December 2013, medical students enrolled at the University of Bologna and at Brown University were recruited via email to answer survey questions asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
0
23
2
2
Order By: Relevance
“…It is also similar to the prevalence of 17.2% found in a worldwide literature review on 74,001 questionnaires from 1988 to 2013 (Roncero et al, 2015). In contrast, a higher prevalence of 31% has been reported amongst Italian medical students (La Torre et al, 2012), with lower prevalences seen amongst Spanish resident physicians (6.5%, n=634) (Ranchal Sánchez et al, 2018), and Americans medical students (6%, n= 174) (Armstrong et al, 2017) though the small sample sizes here should be taken into consideration in the interpretation of the results.…”
Section: Discussioncontrasting
confidence: 63%
“…It is also similar to the prevalence of 17.2% found in a worldwide literature review on 74,001 questionnaires from 1988 to 2013 (Roncero et al, 2015). In contrast, a higher prevalence of 31% has been reported amongst Italian medical students (La Torre et al, 2012), with lower prevalences seen amongst Spanish resident physicians (6.5%, n=634) (Ranchal Sánchez et al, 2018), and Americans medical students (6%, n= 174) (Armstrong et al, 2017) though the small sample sizes here should be taken into consideration in the interpretation of the results.…”
Section: Discussioncontrasting
confidence: 63%
“…Therefore, the education of dental students may emphasize more tobacco control of patients [49]. According to present study, Turkish dental and medical students' smoking rates are higher than Lithuanian dental students (12%) and American medical students (6.1%) but lower than that of Italian medical students (29.5%) [33,50]. Previous studies indicated that non-smoking physicians are more successful at getting patients to quit smoking.…”
Section: Original Articlementioning
confidence: 55%
“…Since healthcare professionals have a high impact on patients to establish positive health behavior, future interventions should aim to eliminate tobacco usage among the students [50].…”
Section: Original Articlementioning
confidence: 99%
“…Finalmente, se encontró que el 98.38% considera que se debe realizar educación médica continua en tabaquismo, similar a los hallazgos en otras encuestas que evalúan la necesidad de capacitación por parte del personal de salud y que revelan que más del 90% están de acuerdo con la implementación de este tipo de temas académicos (17,22,35,36); sin embargo, en Kirguistan solo el 63% de los médicos piensa que se requiere más información (37); lo cual se encuentra sustentado en que el entrenamiento a los profesionales de la salud aumentaba la asesoría con la estrategia de las 5As, sobre todo en brindar ayuda, donde el 79.1% de los médicos familiares que tenía entrenamiento en tabaquismo realizaba asesoría a los padres de niños con enfermedades respiratorias y cerca 85% de los profesionales de la salud a nivel de urgencias ofrecían ayuda y asesoría (29,38), cifra que concuerda con el hallazgo de Kats et al, que solo el 5.7% de las enfermeras y el 5.1% realizaba esta intervención antes del entrenamiento, comparado con los datos posteriores donde el 22.5% de las enfermeras y el 18.4% de los médicos realizó la intervención (39).…”
Section: Discussionunclassified